Spremljanje dolgov uporabnikov ter izterjava v splošnih knjižnicah - Košir, Darja (Organizacija znanja, 2022)
Kranj City Library is one of the largest Slovenian public libraries, which, like most Slovenian libraries, also deals with the debts of its users. Prohit Claims Management Agency helps us to collect the debts. Before collection by an external contractor, we first carry out a series of procedures in the library to collect the debts ourselves. We regularly monitor the debts of library users and inform them about their debts. Users can settle their debts in person at the library or online. We analysed the last three years (from August 2019 to August 2022) in more detail because we were interested in how successful the library is in collecting debts, how many debts are written off for various reasons and how efficient the debt management agency is. In the analysis, we were interested in how many cases regarding unreturned items and unpaid debts were handed over to the agency for collection and how many of these cases were successfully resolved. Based on the data analysis, we found that the library collects most of the debts itself. The agency, however, is very successful at resolving the difficult-to-collect receivables that were handed over to them.
Keywords: agencija za upravljanje terjatev; agency for debt collection; izterjava; Kranj City Library; Mestna knjižnica Kranj; payment indiscipline; plačilna nedisciplina; recovery